2013
DOI: 10.1590/s1983-40632013000300008
|View full text |Cite
|
Sign up to set email alerts
|

Interferência de plantas daninhas na cultura do sorgo cultivado em safrinha

Abstract: O sorgo apresenta grande importância na economia mundial, como fonte de energia para a alimentação humana e animal. No sudoeste Goiano, apesar de esta cultura apresentar alto potencial produtivo, a produtividade é baixa, fato atribuído, em grande parte, à interferência do manejo inadequado de plantas daninhas. Objetivou-se, nesta pesquisa, determinar os períodos de interferência de plantas daninhas sobre a cultura do sorgo cultivado em safrinha, no município de Rio Verde (GO). Os tratamentos foram constituídos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 10 publications
1
10
0
5
Order By: Relevance
“…On the other hand, Cabral et al (2013) conducted a research with grain sorghum in Goiás State and found that the optimum period to perform the control is between the emergence of the fifth and ninth leaf. The different CTWRs verified reflect the different ecophysiological traits of these types of sorghum, Figure 4.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, Cabral et al (2013) conducted a research with grain sorghum in Goiás State and found that the optimum period to perform the control is between the emergence of the fifth and ninth leaf. The different CTWRs verified reflect the different ecophysiological traits of these types of sorghum, Figure 4.…”
Section: Resultsmentioning
confidence: 99%
“…Esses efeitos positivos na cultura do feijoeiro são resultados dos manejos realizados no solo, que reduziram a infestação das plantas daninhas. Quando a lavoura é cultivada livre de plantas daninhas, as plantas melhoram tanto o crescimento quanto o rendimento produtivo (CABRAL et al 2013, SIDDIQUI et al 2018.…”
Section: Discussionunclassified
“…The knowledge on weed populations in crops is achieved primarily based on a phytosociological survey, indicated as an important factor in the decision-making process of weed control methods (Soares et al 2011, Lima et al 2016. Furthermore, studies also investigated the intensity of weed interference in crops, which is determined by the floristic composition of the cultivated area, producing specific frequency, density and abundance data, also important in assessing the impacts of weeds on farm management systems (Kuva et al 2003, Cabral et al 2013. These assessments are useful in establishing the weed population to determine the most important species to control (Cabral et al 2013, Rodrigues et al 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, studies also investigated the intensity of weed interference in crops, which is determined by the floristic composition of the cultivated area, producing specific frequency, density and abundance data, also important in assessing the impacts of weeds on farm management systems (Kuva et al 2003, Cabral et al 2013. These assessments are useful in establishing the weed population to determine the most important species to control (Cabral et al 2013, Rodrigues et al 2017. As such, this study aimed to assess the effects of soil solarization and mulching to control weeds in the cowpea crop.…”
Section: Introductionmentioning
confidence: 99%